Pengaruh Lokasi Usaha Dan Kualitas Layanan Terhadap Loyalitas Melalui Kepuasan Konsumen Di AHASS Adi Jaya Motor Malang - Nadzhira Auliya Masyhudi; Eka Farida; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study investigates the influence of business location and service quality on customer loyalty, with customer satisfaction as an explanatory variable, at AHASS Adi Jaya Motor Malang. The research is motivated by the growing competition in the motorcycle service industry, which requires authorized workshops to maintain customer loyalty through superior service performance. A quantitative associative approach was employed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method. Data were collected through online questionnaires from 81 respondents selected using purposive random sampling. The findings indicate that business location and service quality have a positive and significant effect on customer satisfaction. Customer satisfaction also shows a positive and significant influence on customer loyalty. Furthermore, customer satisfaction plays an important role in explaining the relationship between business location and service quality with customer loyalty. These results suggest that a strategic and easily accessible location, supported by consistent and reliable service quality, contributes to positive customer evaluations and encourages repeat service usage. Therefore, AHASS Adi Jaya Motor Malang is advised to improve location accessibility, maintain customer comfort, and continuously enhance employee competence and service responsiveness to strengthen long-term customer loyalty. Keywords: Business Location, Service Quality, Customer Satisfaction, Customer Loyalty, AHASS.